Drug-induced parkinsonism in a patient with DiGeorge syndrome: a case report - Cerejo, Clancy; De Cleene, Nicolas; Walser, Gerald; Djamshidian, Atbin; Seppi, Klaus; Heim, Beatrice (Frontiers in Neuroscience, 2024)
DiGeorge syndrome, also referred as 22q11.2 deletion syndrome is a multisystem disorder associated with an increased risk of early-onset parkinsonism. In this case report, we present a case of a 47-year-old male patient with complex comorbidities and seizures. This patient presented with increased seizure frequency and on examination was found to have parkinsonism. Due to the symptoms constellation, a genetic analysis was done which revealed presence of DiGeorge syndrome. However, his DaTscan was normal and hence a possibility of medication induced parkinsonism was considered. Through this case report, we want to emphasize the fact that while it is important to consider genetic testing for young patients with parkinsonism especially in those with complex comorbidities, other possible causes of parkinsonism should not be ignored.